Improving the Ability to Understand the Concept of Sociology Through the Application of Discovery Learning Model Assisted by Augmented Reality Media in Class X.E1 at SMA Negeri 1 IV Nagari Bayang Utara - Indah Purnama Sari; Eka Asih Febriani (Dinasti Publisher, 2025)
At SMAN 1 IV Nagari Bayang Utara, many students have not understood the concepts of sociology, so that learning objectives are not achieved optimally. This is due to the low mastery of concepts, lack of student activeness, limited variations in learning media, and the lack of an effective learning model to strengthen student understanding. This study aims to describe the improvement of students' concept understanding ability through the application of discovery learning model assisted by augmented reality in sociology learning. This research is a Classroom Action Research (PTK) with the aim of improving the learning process and increasing the understanding of sociology concepts in the material of Social Values and Norms. This research was conducted in 2 cycles with each cycle consisting of 3 meetings. The research subjects were students of class X. E 1 SMAN 1 IV Nagari Bayang Utara which amounted to 26 people. The results showed that there was an increase in understanding of concepts in the material of social values and norms as seen from the level of completeness of Achievement of Learning Objectives (KKTP) from pre-action (pretest) of 8.69% with an average of 66.86 then in cycle I rose to 50% with an average of 75.96 and rose to 76% with an average of 80 in cycle II.